Appropriate Nurse Staffing Levels for U.S. Nursing Homes. (June 2020) - Harrington, Charlene; Dellefield, Mary Ellen; Halifax, Elizabeth; Fleming, Mary Louise; Bakerjian, Debra
US nursing homes are required to have sufficient nursing staff with the appropriate competencies to assure resident safety and attain or maintain the highest practicable level of physical, mental, and psychosocial well-being of each resident. Minimum nurse staffing levels have been identified in research studies and recommended by experts. Beyond the minimum levels, nursing homes must take into account the resident acuity to assure they have adequate staffing levels to meet the needs of residents. This paper presents a guide for determining whether a nursing home has adequate and appropriate nurse staffing. We propose five basic steps to: (1) determine the collective resident acuity and care needs, (2) determine the actual nurse staffing levels, (3) identify appropriate nurse staffing levels to meet residents care needs, (4) examine evidence regarding the adequacy of staffing, and (5) identify gaps between the actual staffing and the appropriate nursing staffing levels based on resident acuity. Data sources and specific methodologies are analyzed, compared, and recommended. The goal is to assist nursing home nurses and administrators to ensure adequate nursing home staffing levels that protect resident health, safety, and well-being.